Optical access networks and advanced photonics technologies and deployment strategies - Chochliouros, Ioannis P.; Heliotis, George A. (Premier reference source, 2010)
"This book presents a comprehensive overview of emerging optical access network solutions to efficiently meet the anticipated growth in bandwidth demand" - Provided by publisher